2021
DOI: 10.1111/os.13152
|View full text |Cite
|
Sign up to set email alerts
|

Management of Locked Posterior Shoulder Dislocation with Reverse Hill–Sachs Lesions via Anatomical Reconstructions

Abstract: Objective: To evaluate the outcomes of locked posterior shoulder dislocation with reverse Hill-Sachs lesions in patients treated with anatomical reconstructions.Methods: Patients who were treated at our institution between January 2016 and June 2020 were retrospectively reviewed. The demographics of the patients including gender, age, occupation, and dominant arm were recorded. Eleven cases from 10 patients qualified in this study. Nine males and one female were included. The mean age of the patients was 44.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Out of these, 61 studies were excluded because they were case reports, technical notes or did not meet the inclusion criteria. Ultimately, 14 studies were included in the review, consisting of nine retrospective [ 7 , 8 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and five were prospective [ 28 , 29 , 30 , 31 , 32 ]. A summary of the study selection process is reported in the PRISMA diagram (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of these, 61 studies were excluded because they were case reports, technical notes or did not meet the inclusion criteria. Ultimately, 14 studies were included in the review, consisting of nine retrospective [ 7 , 8 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and five were prospective [ 28 , 29 , 30 , 31 , 32 ]. A summary of the study selection process is reported in the PRISMA diagram (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A summary of the study selection process is reported in the PRISMA diagram (Figure 1 ). Regarding the investigated procedures, seven studies reported the results of McLaughlin procedures and seven reported the results of humeral reconstruction by defect filling with femoral head [ 25 , 31 ] or humeral head [ 8 , 26 ] allograft or iliac crest autograft [ 28 ] or both [ 7 , 27 ]. The evaluation with the mCMS showed an overall poor quality of the included articles with a mean of 67.3 (range 57–82).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guehring et al performed arthroscopic elevation of an impacted lesion, reporting excellent PROMs in 5 patients with minimum 5-year follow-up, with no recurrent instability 61 . Finally, Mi et al reported on an open disimpaction and fixation technique, reporting excellent PROMs and forward elevation in 11 patients at 2-year follow-up 45 . In conclusion, disimpaction and fixation seems to be a viable treatment option for moderate-sized RHSLs with excellent early to midterm postoperative outcomes; however, the strength of these conclusions is limited by the small overall sample sizes available in the literature.…”
Section: Rhsls and Bipolar Bone Lossmentioning
confidence: 99%
“…Bipolar bone loss is also more difficult to treat, and Moroder et al have shown that there is a higher risk of an engaging RHSL for every additional millimeter of posterior glenoid bone loss 22 . Several authors have attempted to develop a treatment algorithm for these injuries according to the literature 43,44 or have described the outcomes of various treatments in their own patients, but no widely accepted consensus has been established to date 45-47 . The most important factor for clinical decision-making is the defect size measured using the best-fit-circle.…”
Section: Rhsls and Bipolar Bone Lossmentioning
confidence: 99%